1967
DOI: 10.1099/0022-1317-1-4-509
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat on the Anatomy of the Adenovirus

Abstract: SUMMARYWhen purified preparations of adenovirus type 5 were heated the icosahedral capsid of the virus was ruptured at the twelve vertices, allowing the viral DNA to become accessible to the action of DNAse. The viral DNA could then be substantially separated from protein by digestion with trypsin or pronase. An analysis of the distribution of viral DNA by radioactivity and the various capsid complement-fixing antigens after density gradient centrifugation of heated virus suggested the presence of some other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
1

Year Published

1967
1967
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 18 publications
6
55
1
Order By: Relevance
“…We employed our SRM method to compare protein levels in intact and heated viruses. The data clearly demonstrated the release of the capsid vertices observed earlier (30,49) and revealed the extent to which additional capsid proteins are released. Moreover, we showed evidence for a strong release of the terminal domains of pVI and pVIII generated by AVP mediated cleavage, suggesting a possible role of these protein fragments in escape from the endosome to the host cytosol.…”
Section: Discussionmentioning
confidence: 63%
“…We employed our SRM method to compare protein levels in intact and heated viruses. The data clearly demonstrated the release of the capsid vertices observed earlier (30,49) and revealed the extent to which additional capsid proteins are released. Moreover, we showed evidence for a strong release of the terminal domains of pVI and pVIII generated by AVP mediated cleavage, suggesting a possible role of these protein fragments in escape from the endosome to the host cytosol.…”
Section: Discussionmentioning
confidence: 63%
“…Since no reaction was obtained with freshly prepared virus suspensions containing intact vMons, it may be concluded that at least some of the antigen detectable as the P antigen is incorporated either into or within the viral capsid. The external features of the virion appear to be satisfactorily explained in terms of hexons and pentons (Valentine & Pereira, 1965) and it therefore seems more likely that the P antigen should reside inside the capsid. However, the antigen could be an integral part of the capsid which has not been morphologically recognized and which may only be revealed antigenically on ageing in a similar fashion to the fibre and penton base antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of this work it became obvious that a serological test more sensitive than complement fixation would be of considerable value in detecting antigenicity in the virus particle, and use has been made of the fact that the virus particles readily agglutinate in the presence of anti-viral sera (Valentine & Pereira, 1965). Since the aggregates of virus and antisera sediment much faster than the virus alone an indication of the extent of agglutination can be obtained by incubating antiserum with virus labelled with 3H and centrifuging at a speed which deposits aggregates but not the virus.…”
Section: Methodsmentioning
confidence: 99%
“…These were prepared from adenovirus-infected KB cells after fluorocarbon extraction and CsCl density gradient centrifugation (Russell et al, 1967). The material above the opalescent virus band containing the "soluble" antigens was dialysed against phosphate-buffered saline (PBS) before use.…”
Section: Methodsmentioning
confidence: 99%